Novel Siprulina platensis Bilosomes for Combating UVB Induced Skin Damage - Mariam Zewail; Passent M. E. Gaafar; Nancy Abdel Hamid Abou Youssef; Merhan E. Ali; Mai F. Ragab; Miranda F. Kamal; Mohamed H. Noureldin; Haidy Abbas (MDPI AG, 2022)
The recent interest in bioactive compounds from natural sources has led to the evolution of the skin care industry. Efforts to develop biologically active ingredients from natural sources have resulted in the emergence of enhanced skin care products. Spirulina (SPR), a nutritionally enriched cyanobacteria-type microalga, is rich in nutrients and phytochemicals. SPR possesses antioxidant, immunomodulatory, and anti-inflammatory activities. Spirulina-loaded bilosomes (SPR-BS), a novel antiaging drug delivery system, were designed for the first time by incorporation in a lecithin-bile salt-integrated system for bypassing skin delivery obstacles. The optimized BS had good entrapment efficiency, small particle size, optimal zeta potential, and sustained drug release pattern. Blank and SPR-loaded BS formulations were safe, with a primary irritancy index of <2 based on the Draize test. In vivo tests were conducted, and photoprotective antiaging effects were evaluated visually and biochemically by analyzing antioxidant, anti-inflammatory, and anti-wrinkling markers following ultraviolet (UV) B irradiation. Results of biochemical marker analysis and histopathological examination confirmed the superior antiaging effect of SPR-BS compared with SPR. Thus, SPR-loaded BS is a promising nanoplatform for SPR delivery, can be used for treating UV-induced skin damage, and offers maximum therapeutic outcomes.